The Case of a Patient with Concomitant Popliteal Artery and Ascending Aortic Aneurysm Who Presented with the Blue Toe Syndrome - Gunes, Tevfik; Alur, Ihsan; Girgin, Serkan; Emrecan, Bilgin (Annals of Medical Research, 2021)
None